Upper Pedicle Breast Flap - Antônio Roberto Bozola; Alexandre Caroni Bozola (Revista Brasileira de Cirurgia Plástica, 2020)
Introduction: Here we propose a tactic to fill the upper poles of breasts that are emptied by ptosis in primary and secondary cases to obtain anatomically beautiful breasts with sufficient breast volume. Objective: To describe breast tissue flaps used to fill the upper breast pole when there is adequate or surplus volume. Methods: In primary or secondary cases, if the measurement from point A to the submammary fold is long and that to the upper glandular ridge is short, one obtains from the difference between them a flap with an upper pedicle, termed a “book leaf,” and sutured at the upper mammary pole. Glandular detachment preserves the skin’s thickness with subcutaneous tissue in all maneuvers similar to the adjacent thorax according to the mammary gland’s vascular anatomy, which is irrigated and innervated from the subcutaneous tissue to the gland. Results: The six patients presented no complications related to flap irrigation. Adequate mammary shape and volume were achieved by inverting measurements between the lower and upper poles. Discussion: Here we proposed an innovative manner to fill the upper pole of the breast with a breast upper pedicle flap. A larger number of cases should be analyzed in the long term. Conclusion: The flap is used to fill the upper pole of the breast when the largest volume is in the lower pole.